2003
DOI: 10.1097/01.sap.0000069073.38391.91
|View full text |Cite
|
Sign up to set email alerts
|

How Accurate Is Frozen Section for Skin Cancers?

Abstract: Frozen section analysis has been used to increase the likelihood of complete excision of skin cancers and to minimize the risk for recurrence. The question of its accuracy has been addressed in many studies and this article adds data to the discussion. A retrospective study was performed of 60 consecutive cases in which frozen section diagnoses were compared with permanent sections. It was found that in 85% of the cases the frozen sections were accurate compared with the permanent sections, but in 13% of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 3 publications
3
38
0
1
Order By: Relevance
“…The findings confirm the use of FS evaluation of margin in some patients suffering from SCC and BCC cancers of the head and neck (9,15,16). One study (17), reported the positive predictive value of subareolar FS is 100%, negative predictive value 83%, sensitivity 38%, and specificity 100%.…”
Section: Discussionsupporting
confidence: 72%
“…The findings confirm the use of FS evaluation of margin in some patients suffering from SCC and BCC cancers of the head and neck (9,15,16). One study (17), reported the positive predictive value of subareolar FS is 100%, negative predictive value 83%, sensitivity 38%, and specificity 100%.…”
Section: Discussionsupporting
confidence: 72%
“…There were no positive margins in paraffin block in any of our patients. Some other centers do not rely on the results of frozen section and prefer delayed reconstruction after negative paraffin block [1,16]. However, in those centers patients who presented this diagnostic dilemma had angiosarcoma and melanocytic tumors and were among those receiving radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The frozen section is an optional tool utilized to intra-operatively assess one or more margins of a surgically excised specimen. Its advisability, reliability and effectiveness are as debated as Mohs micrographic surgery with a corresponding equal distribution of supporters and detractors (8)(9)(10)(11)(12)(13)(14).…”
Section: Frozen Section ---------------------------------------------mentioning
confidence: 99%
“…The use of intra-operative frozen section remains controversial in the surgical treatment of non-melanoma skin cancer, being commonly considered an optional tool, the reliability and effectiveness of which remain questionable (8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%